2011
DOI: 10.1007/s11062-011-9160-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Infradian Rhythmics of Thermal/Pain Sensitivity of the Helix Mollusc under the Action of Electromagnetic Fields

Abstract: We measured characteristics of thermal/pain (th/p) sensitivity of Helix albescens (threshold and latency of the avoidance behavioral reaction) under conditions of the hot-plate test. As was found, weakening (shielding) of the background electromagnetic field, as well as the action of low-intensity radiations of extremalfrequency ranges, induced two-phase changes of these characteristics within a 21-day-long observation period with different manifestations and durations of the phases. Initial increase in the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In the case of the action of low-frequency OMF, the 1st (hyperalgesic) phase was mild and short (about 3 days); in contrast, the subsequent hypoalgesic effect was much more intense and long-lasting (its duration exceeded the observation period in our experiments). In general, results of the present experiments agree rather well with the data obtained in our preceding work [1].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the case of the action of low-frequency OMF, the 1st (hyperalgesic) phase was mild and short (about 3 days); in contrast, the subsequent hypoalgesic effect was much more intense and long-lasting (its duration exceeded the observation period in our experiments). In general, results of the present experiments agree rather well with the data obtained in our preceding work [1].…”
Section: Discussionsupporting
confidence: 93%
“…Earlier, we observed complex multiphase changes in thermonociceptive sensitivity of terrestrial pulmonary mollusks, Helix albestens, which were manifested under conditions of shielding from background electromagnetic fields (EMFs) and action of weak oscillating magnetic fields (OMFs) of an extremely low-frequency (ELF) range [1]. It should, however, be recognized that elucidation of the mechanisms responsible for changes in the thermonociceptive sensitivity under the action of the above factors and also of EMFs with other characteristics remains in the initial stages.…”
Section: Introductionmentioning
confidence: 99%
“…S4 (ESI). † 45,53 The corresponding results are further summarized in Table S3 (ESI). † Compared with other tissues, the skin is more densely dominated by nociceptors, and they are widely distributed in the dermis of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Each work reviewed is unique and, therefore, not replicated by an independent scientific group. Rare exclusion is HMF nociception studies reported in [ 71 , 81 , 92 , 97 ] and [ 112 , 114 , 132 , 152 ]. Non-reproducibility is a common problem in laboratory magnetobiology.…”
Section: Experimental Datamentioning
confidence: 99%